Measuring the natural environment - Strangeways, Ian, 1932- (Cambridge University Press, 2000)
Annotation Measurements of natural phenomena are vital for any type of environmental monitoring, from the practical day-to-day management of rivers and agriculture, and weather forecasting, through to longer term assessment of climate change and glacial retreat. This book looks at past, present and future measurement techniques, describing the operation of the instruments used and the quality and accuracy of the data they produce. The book will be important for all those who use or collect such data, whether for pure research or day-to-day management of the environment. It will be useful for students and professionals working in a wide range of environmental science: meteorology, climatology, hydrology, water resources, oceanography, civil engineering, agriculture, forestry, glaciology, ecology.